PERAN HIDROKSIAPATIT SEBAGAI BONE GRAFT DALAM PROSES PENYEMBUHAN TULANG - Hengky B Adrianto (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2011)
The reconstruction of bone defects remains a challenge for the oral surgeon until now, because the healing process is often susceptible to interference or even failure. To assist the process of bone healing, do therapy by using a material or the bone graft substitute material. Bone graft should have three basic functions such as osteogenesis, osteoinduction and osteoconduction. The high level of bone graft demands led to the researchers and surgeons continue to develop biomaterials as an alternative. The use of autografts is still the gold standart for the restoration of bone defects.One of the bioceramics are frequently used in biomedical applications as an ingredientsubstitution therapy or bone graft is a synthetic hydroxyapatite. The composition of hydroxyapatite crystals have an overview identical to hydroxyapatite in bone. This material is biocompatible, osteokonduktif, and can be fused with the bone so that it can improve the process of bone regeneration.